Everyone is watching - Gudenkauf, Heather (Park Row Books, 2024)
"From the New York Times best-selling author of The Overnight Guest comes a twisty locked-room thriller about a mysterious, high-stakes game show that proves life-threatening. The Best Friend. The Confidant. The Senator. The Boyfriend. The Executive. Five contestants have been chosen to compete for ten million dollars on the game show One Lucky Winner. The catch? None of them knows what (or who) to expect, and it will be live streamed all over the world. Completely secluded in an estate in Northern California, with strict instructions not to leave the property and zero contact with the outside world, the competitors start to feel a little too isolated. When long-kept secrets begin to rise to the surface, the contestants realize this is no longer just a reality show--someone is out for blood. And the game can't end until the world knows who the contestants really are..."--